Renal transplant outcomes in primary FSGS compared with other recipients and risk factors for recurrence: A national review of the Irish Transplant Registry. Issue 1 (4th December 2017) - Cormican, Sarah; Kennedy, Claire; O'Kelly, Patrick; Doyle, Brendan; Dorman, Anthony; Awan, Atif; Conlon, Peter
Abstract: Introduction: Primary focal segmental glomerular sclerosis (p‐FSGS) is commonly complicated by recurrence (r‐FSGS) post‐transplantation. Our objective was to describe Irish outcomes for transplantation after end‐stage renal disease (ESRD) due to p‐FSGS, specifically rates of, and treatments for, r‐FSGS. Patients and Methods: Irish patients with biopsy‐proven FSGS were identified from the Irish National Kidney Transplant database (1982‐2015). Medical record review was performed to identify predictors of r‐FSGS and treatments for r‐FSGS. Transplant outcomes were compared to outcomes in all renal transplants performed during the same time period using registry data. Demographic and clinical predictors of r‐FSGS were identified. Statistical analysis was performed using Stata (version 13, College Station, TX, USA). Results: Thirty‐eight transplant recipients had biopsy‐proven p‐FSGS, 16 received a second transplant. A total of 3846 transplants formed the comparator group. r‐FSGS complicated 60.5% (23/38) of first transplants. Eighty‐six percent (10/12) of patients with previous r‐FSGS developed recurrent disease after further transplantation. Patients with p‐FSGS receiving a first renal transplant had higher rate of graft failure than those with another cause of ESRD (HR 1.9, 95% CI 1.152‐3.139). Sixteen patients received immunotherapy for r‐FSGS; 12 (86%) had at least partial response, but two (14%) developed significant complications. Discussion: We demonstrate high rates of r‐FSGS and describe modest success from with treatments for r‐FSGS.